EVALUATING THE EFFECTIVENESS OF MICROLEARNING DURING ONBOARDING TO ENHANCE COMPETENCY OF FRONT LINERS IN A SYARIAH MICROFINANCING BANK - Linda Noviana Mandagie; Achmad Ghazali (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The fact that more than half of the new Community Officers at Bank Syariah Nasional leave the company within their first three months is a big problem. A lot of these early resignations can be traced back to the fact that rookie officers had a hard time meeting performance goals during this time. To meet this challenge, BSN has put in place a twenty-one-day onboarding program that includes microlearning using the Learning SHARIA mobile app. This strategy can be used with employees who are located in different parts of the world, and it is scalable. However, its speediness in accelerating the acquisition of early skills has not been well-tested yet. This paper examines how microlearning can be used to promote the perception of competence in the context of the onboarding process as well as the mediating role of motivation and supervisory support in this specific interaction. The information collected on 392 participants was analyzed using a Partial Least Squares Structural Equation Modeling approach. The findings indicate that exposure to microlearning in itself does not play a significant role in improving the level of competence. The effect of the use of smart devices can be observed when learning activities are effectively used to influence the motivation of learners, which in turn results in a significant direct positive impact on perceived competence. Supervisor support is also ranked as a key determinant, as it has a direct impact on the motivation of learners, and the top management approval is essential to the successful use of microlearning programs. Remarkably, the completion of modules, learning days on the platform, and quiz grades are considered insufficient measures of real learning results in this specific situation. The research finds that microlearning is effective, but it requires support from supervisors who can inspire and direct new employee. Practical recommendations include refining onboarding indicators in line with the Kirkpatrick evaluation model, applying the Pareto principle to identify and prioritize the most influential learning modules, and enhancing coaching practices among supervisors.